2019
DOI: 10.21037/acr.2019.07.06
|View full text |Cite
|
Sign up to set email alerts
|

Perforated ileus after L5-S1 anterior lumbar interbody fusion: a case report presentation

Abstract: Acute colonic pseudo-obstruction (ACPO) as a result of anterior lumbar spinal surgery can result in colonic perforation. ACPO is often treated successfully with conservative measures, reserving surgical intervention for severe cases. The most severe cases can result in colonic perforation with a concomitant high mortality rate. Herein we outline a case of a 72-year-old male with multiple medical comorbidities and history of intermittent constipation who underwent anterior lumbar interbody fusion (ALIF) of L5-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rates of postoperative ileus in ALIF patients vary in the literature, with between 2 and 58% reported [60], most commonly occurring between 2 and 5.4% [43], and occurring in both transperitoneal and retroperitoneal approaches [68]. Open ALIF approaches in this review had higher rates of postoperative ileus reported compared to laparoscopic procedures, with no significant difference between transperitoneal and retroperitoneal approaches (3.54% vs. 2.60%; p > 0.05).…”
Section: Postoperative Ileusmentioning
confidence: 65%
“…Rates of postoperative ileus in ALIF patients vary in the literature, with between 2 and 58% reported [60], most commonly occurring between 2 and 5.4% [43], and occurring in both transperitoneal and retroperitoneal approaches [68]. Open ALIF approaches in this review had higher rates of postoperative ileus reported compared to laparoscopic procedures, with no significant difference between transperitoneal and retroperitoneal approaches (3.54% vs. 2.60%; p > 0.05).…”
Section: Postoperative Ileusmentioning
confidence: 65%
“…In this case, the sigma lesion was not noticed and repaired during the ALIF surgery, and that was the trigger for the peritonitis and septic shock that occurred later. Mahoney, et al [13] described a case of a 72-yearold male who, 5 days after an ALIF surgery, developed an acute colonic pseudo-obstruction which later led to a colonic perforation that had to be surgically repaired. In this case however, the colonic injury did not take place during the surgery.…”
Section: Case Reportmentioning
confidence: 99%
“…15 Other ALIF complications that have been described include ureter injury, neurological injury, postoperative ileus, colonic pseudoobstruction, superficial infection, urinary tract infection, sepsis, subsidence, pseudarthrosis, instrumentation failure, adjacent segment disease, sacral fractures, and retroperitoneal fluid collections. 10,[16][17][18][19][20][21][22][23][24] Retroperitoneal fluid collections are an uncommon cause of delayed symptoms following an ALIF procedure. Various etiologies include hematomas, urinomas, chyloperitoneum, cerebrospinal fluid (CSF) collections, and deep infections.…”
mentioning
confidence: 99%